Preliminary investigations on transmission and life cycle of the ear mites of the genus Raillietia trouessart (Acari: Gamasida) parasites of cattle - Arlindo Luis da Costa; Rômulo Cerqueira Leite; João Luiz Horacio Faccini (Memorias do Instituto Oswaldo Cruz, 1992)
The life cycle of ear mites of the genus Raillietia Trouessart consists of egg, larva, proto-and deutonymph and adult. The proto-and deutonymph are free living, non feeding instars. The teneral adult is the transfer stage. The minimum period required for completion of the life cycle is approximately eight days.